PERAN WEDDING ORGANIZER DALAM PENGELOLAAN TIM DAN PENGENALAN LAYANAN PADA ACARA NIKAH MASSAL - Jein Eyllafan B Love; Sugito Sugito (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Mass weddings are social events involving many couples from limited economic backgrounds, requiring professional event management. This community service project aims to analyze the role of wedding organizers in team management and service introduction strategies for mass weddings. The method used was a participatory approach involving the wedding organizer team, participants, and vendors through coordination stages, simulation practices, and technical briefing sessions. The results of the activity indicate that wedding organizers play a key role in organizing the event flow (rundown), managing human resources through a clear division of liaison officers (LOs), and serving as an effective communication link between participants and external parties, such as the registrar. Service introductions are conducted in an educational manner through quality direct assistance, which contributes to participant satisfaction and builds a positive image of the service provider. Structured team management has been proven to minimize technical obstacles and ensure that the marriage ceremony is carried out in accordance with applicable laws and administration. In conclusion, the role of wedding organizers is crucial in increasing the operational effectiveness of large-scale social events. Through this experience, the team can strengthen its professionalism and social contribution in supporting government programs to legalize community marriage. Thorough coordination and integration are key to creating a sustainable, sacred, and joyful moment for mass wedding participants. ABSTRAK Acara nikah massal merupakan kegiatan sosial yang melibatkan banyak pasangan dengan latar belakang keterbatasan ekonomi, sehingga memerlukan manajemen acara yang profesional. Pengabdian masyarakat ini bertujuan untuk menganalisis peran wedding organizer dalam pengelolaan tim dan strategi pengenalan layanan pada acara nikah massal. Metode yang digunakan adalah pendekatan partisipatif yang melibatkan tim wedding organizer, peserta, dan vendor melalui tahapan koordinasi, praktik simulasi, serta sesi briefing teknis. Hasil kegiatan menunjukkan bahwa wedding organizer berperan sebagai koordinator utama dalam mengatur alur acara (rundown), mengelola sumber daya manusia melalui pembagian divisi liaison officer (LO) yang jelas, dan menjadi penghubung komunikasi efektif antara peserta dengan pihak eksternal seperti penghulu. Pengenalan layanan dilakukan secara edukatif melalui kualitas pendampingan langsung, yang mampu menciptakan kepuasan peserta dan membangun citra positif perusahaan jasa tersebut. Pengelolaan tim yang terstruktur terbukti meminimalisir kendala teknis dan memastikan prosesi akad berjalan sesuai hukum serta administrasi yang berlaku. Kesimpulannya, peran wedding organizer sangat krusial dalam meningkatkan efektivitas operasional acara sosial berskala besar. Melalui pengalaman ini, tim dapat menguatkan profesionalisme dan kontribusi sosial dalam mendukung program pemerintah guna melegalkan pernikahan masyarakat. Integrasi koordinasi yang matang menjadi kunci utama dalam menciptakan momen bahagia yang sakral bagi para peserta nikah massal secara berkelanjutan.